Analisis Pengaruh Kebijakan Ekonomi Terhadap Kesejahteraan Mahasiswa - Yosep Moan Banda; Maria Klaret Ngina (Ekspektasi: Jurnal Pendidikan Ekonomi, 2025)
This research aims to analyze the influence of government economic policies on the welfare of students in Indonesia, specifically at Flores Ende University. . Student welfare is an important aspect in creating quality human resources. This research uses a qualitative descriptive approach with data collection techniques through in-depth interviews, observation and documentation studies. The research subjects were Flores University students from 2 study programs, namely the management study program and the economic education study program. The research results show that economic policies such as the Indonesia Smart College Card (KIP-K), fuel subsidy policies, inflation and fiscal policy have a significant influence on student welfare. The positive impact can be seen from increasing access to higher education through tuition assistance, however inflation and rising prices of basic necessities have a negative impact on students' purchasing power. This research recommends the need to synchronize economic policies with student needs and increase social assistance programs that are more targeted.